Blinded by science? Reasons for thinking twice - Poulston, JM (Council for Hospitality Management Education (CHME), 2014)
Critical thinking is a key skill promised by many undergraduate programmes, yet few offer specific courses in thinking, nor do university lecturers necessarily think critically or know how to teach critical thinking. This preliminary paper overviews critical thinking in hospitality pedagogy, then uses the literature on fluoridation and astrology to exemplify the discrepancies between observable phenomena and the common view. Empirical data are employed to interrogate the relationship between empiricism and belief, and survey data on contentious beliefs further explore this relationship. The paper concludes that the relationship between scientific evidence and belief is somewhat arbitrary, and advice from friends and personal experience are important influences on thinking and belief. Implications for hospitality and tourism education are addressed.
Keywords: Beliefs; Critical thinking; Education; Paranormal; Reasoning